Partisipasi Waragenet terhadap konten homoseksual di media sosial TikTok - Tabita, Tabita; Formas Juitan Lase (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
TikTok social media has become an active digital space that allows its users to respond to emerging social issues, one of which is homosexuality. In this context, this study aims to understand how netizens participate in homosexual content uploaded by TikTok users, especially the account @ragilmahardika which openly displays same-sex married life. This research uses Henry Jenkins' Participatory Culture theory, which classifies forms of participation in four categories: Affiliations, Expressions, Circulations, and Problem Solving Collaborations. Previous research indicates that Indonesian society shows a complex response to homosexual issues, ranging from support, rejection, to a neutral attitude. The method used in this research is descriptive qualitative with a digital netnography approach, which utilizes data in the form of comments from TikTok video uploads. Through the process of coding, noting, and abstraction, it was found that netizen participation reflects differences in public opinion influenced by religious norms, culture, social values, and individual expression in the internet world.